The Use of Animation Videos to Improve Students’ Speaking Skill - Cut Irmayunda; Sofyan A. Gani; Nira Erdiana (Universitas Syiah Kuala, 2020)
The objective of this study is to figure out whether the use of animation videos improve students’ speaking skill to the second-year students at SMP Negeri 16 Banda Aceh. The method of this study was quantitative research (experimental study) with one group pre-test and post-test design. The sample of this research was one class at VIII-1 which consists of 30 students. The researcher used simple random sampling to determine the sample. The researcher used an oral test to collect the data about giving a dialogue (an expression to invite someone) with their partner. In analyzing the data, the researcher used a statistical formula to measure the data. The calculation result showed that the mean score of students' pre-test score was 21 and the mean score of the post-test was 41. Then, the t-score was 4.89 and the t-table was 2.045. It can be seen that the t-score was higher than the t-table. In conclusion, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. As a result, the use of animation videos in learning English improves students speaking skills.